Multiparametric Assessment of Right Ventricular Dysfunction in Heart Failure: An Analysis From PARAGON‐HF - Henri Lu; Riccardo M. Inciardi; Martin Abanda; Amil M. Shah; Maja Cikes; Brian L. Claggett; Narayana Prasad; Carolyn S. P. Lam; Margaret Redfield; John J. V. McMurray; Marc A. Pfeffer; Scott D. Solomon; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background This study aims to characterize right ventricular dysfunction (RVD) in heart failure (HF) with preserved ejection fraction and understand the cumulative prognostic value of abnormal RV echocardiographic parameters in HF with preserved ejection fraction. Methods and Results Data from 809 patients in the PARAGON‐HF (Prospective Comparison of Angiotensin Receptor–Neprilysin Inhibitor With Angiotensin‐Receptor Blocker Global Outcomes in HF With Preserved Ejection Fraction) echocardiographic substudy (55% women, mean age 74±8 years) were analyzed. Correlates of RVD (defined as tricuspid annular plane systolic excursion <1.7 cm, fractional area change <35% or absolute RV free wall longitudinal strain <20%) were identified using multivariable logistic regression models. We further assessed the prognostic value of the number of abnormal RV parameters (0, 1, ≥2) on total HF hospitalizations (HFH) and cardiovascular death, total HFH, first HFH or cardiovascular death, all‐cause death, and cardiovascular death. RVD was identified in 461 (57%) patients. Correlates of RVD included older age, higher heart rate, atrial fibrillation/flutter, greater left ventricle wall thickness, higher N‐terminal pro‐B‐type natriuretic peptide levels, lower systolic blood pressure, and lower left ventricle absolute global longitudinal strain. These results were consistent across sexes, except atrial fibrillation/flutter and LV wall thickness, which were associated with a higher risk of RVD in men but not in women. Participants with ≥2 abnormal RV parameters had a significantly higher adjusted risk of total HFH and cardiovascular death (rate ratio, 2.13 [95% CI, 1.13–4.01]), first HFH or cardiovascular death, all‐cause death, and cardiovascular death. Conversely, an isolated abnormal RV parameter was not associated with a worse outcome. Conclusions RV measures may underestimate the burden of RVD in HF with preserved ejection fraction when considered in isolation. Clinicians should consider multiple dimensions to comprehensively assess RV function in patients with HF with preserved ejection fraction.